(untitled) (The Insight, 2025)
Background: Complementary feeding, which involves introducing additional foods and liquids alongside breast milk when it alone is insufficient, is crucial for fulfilling infants’ nutritional needs. The purpose of this study was to examine the impact of media, family, socio-cultural influences, and immunization counseling on complementary feeding practices among mothers. Aim of the study: The aim of the study was to assess the impact of media, family, socio-cultural influences, and immunization counseling on complementary feeding practices among mothers. Methods & Materials: This cross-sectional study was conducted from September to December 2009 at the Paediatric Inpatient and Outpatient Departments of Dhaka Shishu Hospital and the Institute of Child Health & Shishu Sasthya Foundation Hospital (ICH & SSFH), Mirpur-2, Dhaka. Data were collected from 400 mothers of children aged 6 months to 2 years using a structured questionnaire on complementary feeding practices. Data were analyzed using SPSS v12.0; p < 0.05 was considered significant. Results: Among 400 mothers, timely feeding was higher with immunization counseling (54.4% vs. 41.9%, p<0.001), neighbor/media influence (59.2% vs. 29.4%, p<0.001), higher education (60.3% vs. 36.1%, p<0.001), and antenatal counseling (63.8% vs. 35.9%, p<0.001). Feeding ≥3 times/day and appropriate consistency were also significantly better in these groups. Conclusion: Improving maternal education, counseling, and media engagement is key to promoting appropriate complementary feeding practices from 6 months of age.